Apart but Connected: Online Tutoring, Cognitive Outcomes, and Soft Skills - Carlana, Michela; La Ferrara, Eliana (American Economic Review, 2025)
We study the Tutoring Online Program (TOP), where tutoring is entirely online and tutors are volunteer university students matched with underprivileged middle school students. We leverage random assignment to estimate effects during and after the pandemic (2020 and 2022), investigating channels of impact. Three hours of individual tutoring per week increased math performance by 0.22 SD in 2020 and 0.20 SD in 2022. Higher dosage yielded stronger effects, while group tutoring smaller effects. TOP enhanced students’ aspirations, socioemotional skills, and psychological well-being, but only during school closures. We also estimate the impact of TOP on tutors, finding an increase in empathy. (JEL I12, I21, I23, I26, I28)